The Threat of Terrorism and the Changing Public Discourse on Immigration after September 11 - Arthur, C. Damien (2014)
This article uses articles from the opinion-leading press to investigate how the news media's repertoire of negative portrayals changed after the September 11 terrorist attacks. It is based on a systematic random sample of 360 articles from two, opinion-leading newspapers---one known for its liberal slant (New York Times) and one known for its conservative slant (Wall Street Journal). The sample is drawn from a large population of articles published over a six-year period (1998-2004). The findings show that the percentage of negative frames involving not only terrorism but also other non-terrorist threats increased significantly after September 11. The elevated frequency of negative frames was found in both the New York Times and the Wall Street Journal, but the increase was significantly greater in the conservative periodical. Immigrants from non-European countries were also significantly more likely to be associated with negative frames than European immigrants. These three variables-national origin, news source, and September 11-were strong predictors of negative frames, even when controlling for other correlates. Suggesting an authoritarian turn in American political discourse, the study highlights cultural factors, as opposed to the conventional psychological explanations, as key determinants of the changing public discussion of immigration after September 11